Brokering the Research–Practice Gap: A typology. Issue 3 (27th August 2015) - Neal, Jennifer Watling; Neal, Zachary P.; Kornbluh, Mariah; Mills, Kristen J.; Lawlor, Jennifer A.
Abstract: Despite widespread recognition of a research–practice gap in multiple service sectors, less is known about how pre‐existing communication channels facilitate the flow of information between researchers and practitioners. In the current study, we applied an existing typology of brokerage developed by Gould and Fernandez (Sociol Methodol 19:89–126, 1989 ) to examine what types of brokerage facilitate information spread between researchers and educational practitioners. Specifically, we conducted semi‐structured interviews with 19 school administrators and staff in two public school districts regarding their experiences searching for information about instructional, health, and social skills programs. Using deductive content analysis, we found evidence of all five types of brokerage identified by Gould and Fernandez (1989 ). However, only three types of brokerage—gatekeepers, representatives, and liaisons—were involved in the flow of information between school administrators and researchers. Moreover, information transfer often occurred in longer chains that involved multiple, distinct types of brokerage. We conclude with the broad implications of our findings for narrowing the research–practice gap by improving researchers' dissemination efforts and practitioners' search for information.